Development of caprine chimeric embryos reconstructed through ES-tetraploid complementation assay - PATHAK, JUHI; KHARCHE, S D; GOEL, ANJANA (The Indian Journal of Animal Sciences, 2019)
The aim of the present study was to evaluate the development of caprine chimeric embryos in different culture media, viz. RVCL and mCR2aa + 10% FBS. Inner cell mass (ICM) from hatched blastocysts of parthenogenetic activated embryos were used to produce ES cell-like cells (103) while 4-cell embryos obtained from IVF were utilized to produce tetraploid embryos (231). The aggregates prepared were randomly divided into 2 groups, viz. Gr 1 (RVCL) (53) and Gr 2 (mCR2aa +10% FBS) (50) followed by culture in humidified atmosphere of 5% CO2 at 38.5°C in a CO2 incubator. Outcome measures were aggregation, 8–16 cell, morula and blastocyst formation. The percentage of aggregation, 8–16 cell, morula and blastocyst in Gr 1 (RVCL) was 83.33±6.00%, 42.24±7.71%,29.59±7.64% and 11.49±5.36%, respectively while the percentage of aggregation, 8–16 cell, morula and blastocyst in Gr 2 (mCR2aa +10% FBS) was 91.66±4.32%, 54.76±7.75%, 22.32±5.75% and 14.58±5.18%, respectively. In conclusion, both the media supported the development of chimeric embryos up to blastocyst.